تأثير التحول الوبائي على زيادة التكاليف الصحية في الجزائر -دراسة حالة ولاية الجزائر العاصمة - radjille, asma (Finance and Business Economies Review, 2018)
In recent years, Algeria has been undergoing a phase of epidemiological change through the transition from mobile diseases (typhoid, hepatitis B / C, AIDS, etc.), which are called diseases of poverty, to non-communicable diseases, called diseases of well-being and wealth, (Such as cancer, diabetes, blood pressure, etc.), among which are cancer, the so-called rebellious cell that has killed many people in the world in general and Algeria in particular. During the study of the case of the spread of each of these diseases in the state of Algiers and its impact on the increase Health costs